Long-term development of overcorrection after femoral derotation osteotomy in children with cerebral palsy - Thielen, Mirjam; Klotz, Matthias C. M.; Wolf, Sebastian Immanuel; Dreher, Thomas (Gait & posture, 2018)
Background - Recent studies showed rates of recurrence of internal rotation gait (IRG) after femoral derotation osteotomy (FDO) up to 40%. Some surgeons even advice overcorrection during FDO to avoid a later recurrence. - Research question - Evaluation of the long-term development of limbs with initial overcorrection after FDO. - Methods - 29 limbs of 20 children (9.9±3.2years at surgery) with IRG, cerebral palsy (CP) and more than 5° external hip rotation postoperatively were included retrospectively. A gait analysis and clinical examination were performed preoperatively (less than one year, E0), postoperatively (9-23 months, E1) and at the long-term follow-up (at least five years postoperatively, E2). Differences between those children that remained overcorrected at E2 and those with a hip rotation within normal range at E2 were evaluated. - Results - At E2 41% of these limbs remained overcorrected, 52% showed a hip rotation within normal range and 7% showed recurrence of IRG. A comparison of those limbs that remained overcorrected and those ending within normal range revealed neither a difference in age at surgery nor in static and dynamic torsional parameters at E0 and E1 except for pelvic rotation. A significantly larger pelvic internal rotation at E1 for those with remaining overcorrection could be identified. - Significance - A general overcorrection during FDO in children with CP to avoid recurrence of IRG cannot be recommended, as 41% remain overcorrected. Preoperative predictors for long-term development couldn't be identified. If pelvic mal-rotation is corrected, hip rotation may change into normal range over the time in combination with the development of a flexed knee gait.